2023
DOI: 10.6007/ijarped/v12-i1/16228
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Introvert and Extrovert Personality towards Students’ Academic Achievement in Primary School

Abstract: This study examines the relationship between introvert and extrovert personality with the students' academic achievement in a primary school located in Malaysia. This study uses a quantitative approach, followed by a descriptive correlation method. Two null hypotheses were formulated to guide the study. The population is 839 students, a random sampling technique was used to determine the sample size of 269 students from Year 1 and Year 2. Eysenck Personality Questionnaire-Revised (EPQ-R) was used to measure th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
2
1
Order By: Relevance
“…This statement is supported by Dean et al (2006) who conducted a study on the influence of personality on training performance among 370 marines at Marine Corps' Recruiters School. But the findings of this study contradict the findings of a study by Surat and Yun (2023) who found that there is no significant relationship between extrovert personality and academic performance of a student.…”
Section: Discussioncontrasting
confidence: 99%
“…This statement is supported by Dean et al (2006) who conducted a study on the influence of personality on training performance among 370 marines at Marine Corps' Recruiters School. But the findings of this study contradict the findings of a study by Surat and Yun (2023) who found that there is no significant relationship between extrovert personality and academic performance of a student.…”
Section: Discussioncontrasting
confidence: 99%
“…The resources derived from family cohesion serve as a protective factor, fostering the positive development of self‐concept (Preston et al, 2016), interdependent self‐construal (W. Y. Cheng et al, 2021), openness to interpersonal intimacy (Coll et al, 2010), and a sense of coherence (Shuang & Mavani, 2023). Consequently, individuals from cohesive families are likely to be better socially adjusted, particularly during challenging times such as the transition to adulthood (Ye et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, families adopted collective coping mechanisms to maintain their quality of life (Fogel et al, 2022) and protect against negative mental health outcomes, including depression, anxiety, and sleep problems (Kye & Hwang, 2020; Ye, Hu et al, 2023)—a group of consequences we hereafter broadly refer to as the psychological stress responses to COVID‐19 (PSRC) (Zhang & Ma, 2020). Moreover, the psychological resources afforded through healthy family relationships to buffer against PSRC likewise enhanced the capacity for increased trust in future relationships (Erikson, 1993) in studies conducted both during and after COVID‐19 (W. Y. Cheng et al, 2021; Kye & Hwang, 2020; Shuang & Mavani, 2023). Thus, we propose the following hypotheses:Hypothesis Family cohesion is positively associated with trust toward others. Hypothesis Family cohesion is negatively associated with PSRC.…”
Section: Introductionmentioning
confidence: 99%